2023
DOI: 10.1002/zamm.202200262
|View full text |Cite
|
Sign up to set email alerts
|

Homotopic solution of the chemically reactive magnetohydrodynamic flow of a hybrid nanofluid over a rotating disk with Brownian motion and thermophoresis effects

Abstract: Due to the synergetic effects of several types of nanomaterials, the primary goal of the hybrid nanofluid is to enhance the energy transport capabilities over a base fluid. Hybrid nanofluids have a wide range of applications in the industrial, technical, and medical industries, including solar heating systems, food processing, microchannel heat sinks (MCHS), and medicines. In this article, the researchers have investigated the water‐based hybrid nanofluid flow comprising silver and alumina nanoparticles past a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Because of the small size of the nanoparticles, Brownian motion is the major mechanism of particle dispersion in nanofluids. Rashid et al [21] demonstrated a homotopic solution to a hybrid nanofluid's chemically reactive magnetohydrodynamic flow across a rotating disc with Brownian motion and thermophoresis effects. Kalpana et al [22] used a computer method to study the magnetohydrodynamic boundary layer flow of a hybrid nanofluid exhibiting thermophoresis and Brownian motion in a nonuniform channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the small size of the nanoparticles, Brownian motion is the major mechanism of particle dispersion in nanofluids. Rashid et al [21] demonstrated a homotopic solution to a hybrid nanofluid's chemically reactive magnetohydrodynamic flow across a rotating disc with Brownian motion and thermophoresis effects. Kalpana et al [22] used a computer method to study the magnetohydrodynamic boundary layer flow of a hybrid nanofluid exhibiting thermophoresis and Brownian motion in a nonuniform channel.…”
Section: Introductionmentioning
confidence: 99%
“…Rashid et al. [21] demonstrated a homotopic solution to a hybrid nanofluid's chemically reactive magnetohydrodynamic flow across a rotating disc with Brownian motion and thermophoresis effects. Kalpana et al.…”
Section: Introductionmentioning
confidence: 99%
“…Von-Karman [14] for the first time performed research on rotating disk. Rashid et al [15] studied the water-based hybrid nanofluid flow containing silver and alumina nanoparticles over a spinning disk with binary chemical reaction and activation energy. Their results show that the hybrid nanofluid has better thermal conductivity than mono nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed a theoretical model that accounts for the basic role of dynamic nanoparticles in nanofluids and uncovered an important factor in size-dependent conductivity between solid/solid composites and solid/liquid suspensions, as well as nanoparticle size and temperature. Rashid et al 4 examined the comparison of hybrid nanofluid past a rotating disk. Chon et al 5 demonstrated an experimental relationship for A l 2 O 3 nanofluid heat transfer as a function of nanoparticle size (varying from 11 to 150 nm nominal diameters) over a wide temperature range (21°C–71°C).…”
Section: Introductionmentioning
confidence: 99%